The soft-gluon limit and the infrared enhancement of the quark-gluon vertex - Orlando Oliveira; Tobias Frederico; Wayne de Paula (European Physical Journal C: Particles and Fields, 2020)
Abstract The Schwinger–Dyson quark equation (SDE) combined with results from lattice simulation for the propagators are used to obtain information on the quark-gluon vertex, taking into account the recent full QCD lattice results for the soft-gluon limit. Its inclusion leads to a clear enhancement of the infrared quark-gluon vertex. We also find that the relative contribution of the quark-ghost kernel to the quark-gluon vertex in the infrared region does not follow the rules from the perturbative analysis of the ultraviolet region. This shows that for QCD the intuition based on perturbation theory does not apply to the full momentum range. The framework developed in the current work provides analytical expressions for all the longitudinal components of vertex taken into account.